Two dimensional switched beam antenna at 28 GHz for fifth generation wireless system - Orakwue, Stella Ifeoma (2016)
Fifth generation (5G) wireless system is expected to enable new device-to-device (D2D) and machine-to-machine (M2M) applications that will impact both consumers and industry. Moreover, for efficient M2M communication, both one dimensional (1-D) and two dimensional (2-D) beam switching is highly needed for high data-rate wireless radio links. A planar array with 2-D beam switching capabilities is highly desirable in 5G system. This thesis proposes a new technique of achieving simple and cost effective 2-D beam switching array antenna at 28 GHz for 5G wireless system. The technique involves lateral cascading of Butler matrix (BM) beamforming network (BFN). However, designing a planar BM at 28 GHz that will allow K-connector is not a trivial issue because the distances between the ports are X/4 electrical length apart. Nevertheless, two branch line coupler (BLC) with unequal ports separation at 28 GHz on a single substrate are designed and applied to design 1-D switched beam antennas based on BLC and 4 * 4 BM. Then two of these antennas are laterally cascaded to achieve 2-D beam switching antenna. This novel concept is the basis for choosing BM BFN in the design. The proposed 1-D array antennas on BLC and BM have wide measured impedance bandwidth of 18.9% (5.3 GHz) and 21.7% (6.1 GHz) and highest gain of 14.6 dBi and 15.9 dBi, respectively. The 2-D switched beam antenna on cascaded BLC has highest realized gain of 14.9 dB, radiation efficiency of 86%, 86.8%, 85.5%, and 83.4% at ports 1 to 4, respectively. The switching range of from -25o to +18° in the x-z plane and from -18o to 24o in the y-z plane, while the 2-D switched beam antenna based on cascaded 4 * 4 BM has switching range of -41o to 43o in the x-z plane and -43o to 42o in the y-z plane with highest realized gain of 14.4 dBi. The proposed antennas have great potentials for 5G wireless communication system applications.